Development of a Spreadsheet-Based Virtual Laboratory to Improve Students' Science Process Skills - Cut Utari Lydia Fitri; Ibnu Khaldun; Abdul Gani; Zulfadli Zulfadli; Mujakir Mujakir (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
The media virtual lab was developed with a spreadsheet that displayed 168 electrolysis reactions and performed reaction calculations. The implementation is done to improve the Science Process Skills (SPS) using the power of media. The design is an application of the model Analysis, Design, Development, Implementation, and Evaluation (ADDIE) of Research and Development (R&D). The VL was validated and revised by three media experts, who gave 88 on a score scale and were categorized as the highly qualified assessment of media, material, and visual communication. VL is used more in experimental classes than in control classes and SPS. Both of these classes include descriptions of tests, while SPS description tests generated normal but distributed data with a value of 0,502>0,05. The Levene test with a value of 0.849>0.05 indicates that the data is homogenous. The VL is there is a significant difference because the result of t test value obtained are 0,000<0x7E>0.05. The percentage score of each indicator from the experimental class is compared with the control class, which has a high percentage of each indicator. The farthest difference is the domain for movement manipulation and procedure implementation skills. This lends evidence to the hypothesis test that using VL can augment SPS.